Improved properties of Oil Palm Trunk (OPT) Laminated Veneer Lumber (LVL) through the inclusion of rubberwood veneers / Kamarulzaman Nordin ... [et al.] - Nordin, Kamarulzaman; W. Samsi, Hashim; Ahmad, Mansur; Jamaludin, Mohd Ariff (Faculty of Applied Sciences, 2004)
Currently, much research efforts were concentrated towards utilizing oil palm trunk as alternative materials to replace or reduce dependency on rubberwood for furniture. In this study, 30 years old oil palm trunk (OPT) that is normally regarded as waste after falling for re-planting is used as raw material in combination with rubberwood veneers for the manufacture of laminated veneer lumber (LVL). Their properties, in terms of bending and compression strength, were evaluated in accordance with the Japanese Agricultural Standard for L VL. It was found that the bending and compression strength were greatly improved as compared to LVL produced entirely from OPT. Significant reduction in strength properties variations between boards was also found when OPT was utilized in the form of LVL. Being a monocotyledonous species, oil palm trunk properties is stipulated of having great variations between the outer parts of the stems and towards the center of the stem. Such results indicated that more uniform board properties could be produced. It was also found that the bending and compression strength of OPT-L VL produced in this study were comparable to the strength properties of solid rubberwood.